1984
DOI: 10.1002/ajmg.1320170121
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid therapy in the fragile X syndrome

Abstract: Two brothers with fra(X) positive X-linked mental retardation (XLMR) were treated with folic acid. Initially a double blind cross-over design was employed followed by a long-term high dose trial. A decrease in the frequency of fra(X) positive cells was observed when low folic acid culture medium was used but not when an FUdR induction system was employed. Selected behavioral characteristics improved in both while receiving folic acid. Decreased hyperactivity, greater attention span, increased motor coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Moreover, patients with inherited defects affecting t h e folate pathways, such as methylenetetrahydrofolate reductase deficiency, a r e often mentally retarded. Treatment with folic acid or folic acid derivatives in fragile X syndrome has been a t t e m p t e d by several groups (Lejeune, 1981;Harpey, 1982;Brown et al, 1983), and clinical studies of its efficacy a r e underway in several additional centers.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, patients with inherited defects affecting t h e folate pathways, such as methylenetetrahydrofolate reductase deficiency, a r e often mentally retarded. Treatment with folic acid or folic acid derivatives in fragile X syndrome has been a t t e m p t e d by several groups (Lejeune, 1981;Harpey, 1982;Brown et al, 1983), and clinical studies of its efficacy a r e underway in several additional centers.…”
Section: Discussionmentioning
confidence: 97%
“…In subsequent controlled and uncontrolled trials, some investigators have found little or no evidence of behavioral or performance improvement (Brown et al 1986, Fisch et al 1988, Froster-Iskenius Ă©tal. 1986, Madison et al 1986, Rosenblatt et al 1985, Webb et al 1990); limited evidence of improvement has been reported by others (Brown et al 1984, Carpenter et al 1983, Gillberg et al 1985, Gustavson et al 1985, Hagerman et al 1986). Gustavson et al (1985) reported that one adult manifested increased aggressiveness and hyperactivity when treated with folie acid (2 mg/kg) in an open trial, and that the behaviors returned to pretreatment levels one month after the folate treatment was discontinued.…”
Section: Folate Supplementation In Fragile X Syndromementioning
confidence: 88%
“…The first vitamin used for the treatment of the FXS was folic acid. Several publications describe the efficacy and safety of treatment with folic acid in people with FXS [70–73]. …”
Section: Discussionmentioning
confidence: 99%